Graphomotor skills in children with prenatal alcohol exposure and fetal alcohol spectrum disorder: A population‐based study in remote Australia. (19th September 2016) - Doney, Robyn; Lucas, Barbara R.; Jirikowic, Tracy; Tsang, Tracey W.; Watkins, Rochelle E.; Sauer, Kay; Howat, Peter; Latimer, Jane; Fitzpatrick, James P.; Oscar, June; Carter, Maureen; Elliott, Elizabeth J.
Abstract : Background/aim: Few studies have examined graphomotor skills in children with prenatal alcohol exposure (PAE) or fetal alcohol spectrum disorder (FASD). Methods: Graphomotor skills were assessed in 108 predominantly Australian Aboriginal children aged 7.5–9.6 years in remote Western Australia using clinical observations (pencil grasp; writing pressure) and standardised assessment tools (the Evaluation Tool of Children's Handwriting; and the Miller Function and Participation Scales – The Draw‐a‐Kid Game). Skills were compared between children (i) without PAE, (ii) PAE but not FASD and (iii) FASD. Results: Most children used a transitional pencil grasp and exerted heavy handwriting pressure (83.3% and 30.6% of the cohort). The percentage of letters (M = 62.9%) and words (M = 73.3%) written legibly was low. Children with FASD were more likely than children without PAE to use a cross‐thumb grasp ( P = 0.027), apply heavy writing pressure ( P = 0.036), be unable to write a sentence ( P = 0.041) and show poorer word legibility ( P = 0.041). There were no significant differences between groups for drawing outcomes, although some children with FASD drew pictures that appeared delayed for their age. There were no significant differences between children without PAE and those with PAE but who were not diagnosed with FASD. Conclusions: Overall, graphomotor skills were poor in this cohort, but children with FASD performed significantly worse than children without PAE. Findings suggest the need for improved occupational therapy services for children in remote regions and evaluation of graphomotor skills in children with PAE.